PERANAN UNIT PAYMENT COLLECTION DALAM MELAKUKAN PENAGIHAN PIUTANG INDIHOME PT. TELEKOMUNIKASI INDONESIA, Tbk WITEL MEDAN - Nurhidayah Nurhidayah; Nur Fadhilah Ahmad Hasibuan (Worksheet : Jurnal Akuntansi, 2022)
Payment Collection has an important role in PT. Telekomunikasi Indonesia, Tbk Witel Medan. Payment Collection has the authority to handle the collection of accounts receivable and cash income from Indihome customers. This unit is tasked with communicating with customers to remind them of their obligations in making payments for current month's bills and past due arrears. This study uses qualitative methods with primary data types. The results showed that the role of Payment Collection is very influential on the cash income of PT. Telekomunikasi Indonesia, Tbk Witel Medan. However, there are obstacles faced both from customers and from companies, such as network damage, customer data input errors and so on. Suggestions from the author for Payment Collection When providing information to customers, sales should adjust the information in accordance with applicable policies at Telkom so that there are no misunderstandings between marketing and billing, and reduce the level of customer complaints